2006
DOI: 10.1007/s00330-006-0519-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anterior ethmoidal artery by 3D dual volume rotational digital subtraction angiography and native multidetector CT with multiplanar reformations. Initial findings

Abstract: Our purpose is to codify the anterior ethmoidal artery (AEA) course and its relationship with adjacent structures. Twenty patients with cerebrovascular disease underwent selective internal carotid dual volume angiography. Fusion of the vascular and bony images was obtained successively on a second console. MDCT of the cranium was performed in all patients. To identify the AEA course, multiplanar CT reformations were obtained. In all cases the entry-point of AEA and its course were identified by means of dual v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 9 publications
(10 reference statements)
1
15
1
Order By: Relevance
“…Souza et al (6) retrospectively reviewed 198 coronal paranasal sinus CT exams with 3 mm contiguous slices, and found that the medial notch of the orbit, anterior ethmoidal sulcus, and anterior ethmoidal canal were seen in all 198 cases, 194 of 198 cases (98%), and 81 of 198 cases (41%), respectively. Başak et al (7) identified the anterior ethmoidal canal in 43% of cases that underwent a coronal plane CT. Pandolfo et al (8) analyzed AEAs in 20 patients with cerebrovascular disease, and another 78 patients with inflammatory disease and polyposis by a 16-slice multislice CT scanner with a 0.7 mm thickness. They also reported the indirect detection of AEA through the visualization of the entry point of the vessel in the ethmoid or the medial notch of the orbit, in all cases n = 20 (100%) on MPR images.…”
Section: Discussionmentioning
confidence: 99%
“…Souza et al (6) retrospectively reviewed 198 coronal paranasal sinus CT exams with 3 mm contiguous slices, and found that the medial notch of the orbit, anterior ethmoidal sulcus, and anterior ethmoidal canal were seen in all 198 cases, 194 of 198 cases (98%), and 81 of 198 cases (41%), respectively. Başak et al (7) identified the anterior ethmoidal canal in 43% of cases that underwent a coronal plane CT. Pandolfo et al (8) analyzed AEAs in 20 patients with cerebrovascular disease, and another 78 patients with inflammatory disease and polyposis by a 16-slice multislice CT scanner with a 0.7 mm thickness. They also reported the indirect detection of AEA through the visualization of the entry point of the vessel in the ethmoid or the medial notch of the orbit, in all cases n = 20 (100%) on MPR images.…”
Section: Discussionmentioning
confidence: 99%
“…In its course through the ethmoid labyrinth, the position of the anterior ethmoidal artery relative to the ethmoidal roof is very variable; the artery thus becomes vulnerable to injury during surgical procedures. 1,2 This artery irrigates the anterior ethmoidal cells and the frontal sinus; it also gives rise to the meningeal vessels in its course along the olfactory fossa, and also descends to the nasal fossa to irrigate the anterior thirds of the nasal septum and the lateral wall of the nose. 1,[3][4][5][6][7][8][9] The anterior ethmoidal artery is an anatomical landmark; its location is important for recognizing structures of difficult access (frontal sinus) and to define the superior limits in surgery (skull base).…”
Section: Introductionmentioning
confidence: 99%
“…The literature provides significant information on the measurement of the distance from the AEA to the nasal columella, 4 middle turbinate recesses, 5,6 and nasal valves; 7,8 data on the artery's anatomy from radiological studies have also been helpful. [9][10][11][12] These studies provide some guidelines to improve the identification and localization of the artery during surgery. Notwithstanding all this research, it is difficult clinically to locate the artery purely based on these data, particularly due to anatomical variations.…”
mentioning
confidence: 99%